2021
DOI: 10.1167/iovs.62.10.30
|View full text |Cite
|
Sign up to set email alerts
|

Tear Proteomics in Keratoconus: A Quantitative SWATH-MS Analysis

Abstract: Purpose To elucidate dysregulated proteins in keratoconus (KC) to provide a better understanding of the molecular mechanisms that lead to the development of the disease using sequential window acquisition of all theoretical mass spectra (SWATH-MS) as a protein quantification tool of the tear proteomic profile. Methods Prospective cross-sectional study that includes 25 keratoconic eyes and 25 healthy eyes. All participants underwent a clinical, tomographic, and aberromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Due to Fe peripheral deposition, it was hypothesized that central unavailability of Fe contributes to KC development, because it works as a cofactor of lysyl hydroxylase (LH), which is required for the collagen crosslinking process. While no significant differences were found in the serum levels of Fe [59], KC patients show lower levels of iron-binding proteins serotransferrin and lactoferrin in tears [47,68] and the corneal epithelium [69], suggesting that iron homeostasis is locally altered in KC cornea. Interestingly, certain polymorphisms of the transferrin gene have been identified as risk factors for KC [70].…”
Section: Mineralsmentioning
confidence: 82%
See 1 more Smart Citation
“…Due to Fe peripheral deposition, it was hypothesized that central unavailability of Fe contributes to KC development, because it works as a cofactor of lysyl hydroxylase (LH), which is required for the collagen crosslinking process. While no significant differences were found in the serum levels of Fe [59], KC patients show lower levels of iron-binding proteins serotransferrin and lactoferrin in tears [47,68] and the corneal epithelium [69], suggesting that iron homeostasis is locally altered in KC cornea. Interestingly, certain polymorphisms of the transferrin gene have been identified as risk factors for KC [70].…”
Section: Mineralsmentioning
confidence: 82%
“…The hypothesis that Vit D deficiency is common in KC patients was confirmed years later when it was shown that KC patients displayed lower serum levels of Vit D when compared to age-matched controls [44][45][46]. Interestingly, KC patients exhibit downregulation of proteins involved in Vit D transport (e.g., Vit Dbinding protein) and activation [47]. Moreover, an association between Vit D deficiency and KC prevalence was suggested in people living in Middle East regions [46].…”
Section: Vitaminsmentioning
confidence: 94%
“…Hopefully, these new tools will help to overcome the limitations related to the small volume of tear samples. To date, there are already numerous ocular (e.g., keratoconus, dry eye, and glaucoma) and systemic conditions (such as diabetes mellitus, thyroid dysfunction, and neurological diseases) that can be detected and evaluated by biomarkers at the lacrimal level [ 125 , 126 ].…”
Section: Ocular Alterations Related To Admentioning
confidence: 99%
“…Recently, our group carried out a quantification approach of the tear proteome of patients with KC and control participants, using for the first time the sequential window acquisition for all theoretical mass spectra to identify the main dysregulated proteins in the tears of patients with KC. 22 In this way, results from the quantitative study revealed that dysregulated proteins were involved in the central processes of the KC pathophysiology, such as inflammation, oxidative stress, matrix proteolysis, and iron homeostasis. 22 However, the qualitative approach followed in this study aims to complement our previous results, trying to overcome the main handicap of quantitative studies (in which it is necessary to recognize a critical number of peptides to achieve protein quantification), and to obtain an even more extensive view of the tear proteomic profile of the patients with KC.…”
mentioning
confidence: 96%
“… 22 In this way, results from the quantitative study revealed that dysregulated proteins were involved in the central processes of the KC pathophysiology, such as inflammation, oxidative stress, matrix proteolysis, and iron homeostasis. 22 However, the qualitative approach followed in this study aims to complement our previous results, trying to overcome the main handicap of quantitative studies (in which it is necessary to recognize a critical number of peptides to achieve protein quantification), and to obtain an even more extensive view of the tear proteomic profile of the patients with KC. Based on these factors, we performed a shotgun analysis to massively identify the tear proteome of patients with KC, which could highlight proteins undetected in the quantitative analysis and enlarge our knowledge of the disease's pathophysiology.…”
mentioning
confidence: 96%